Potassium Bromide Surface Passivation on CsPbI3-xBrx Nanocrystals for Efficient and Stable Pure Red Perovskite Light-Emitting Diodes - Yang, Jun-Nan; Song, Yang; Yao, Ji-Song; Wang, Kun-Hua; Wang, Jing-Jing; Zhu, Bai-Sheng; Yao, Ming-Ming; Rahman, Sami Ur; Lan, Yi-Feng; Fan, Feng-Jia; Yao, Hong-Bin (Journal of the American Chemical Society, 2020)
All-inorganic lead halide perovskite nanocrystals (NCs) are potential candidates for fabricating high-performance light-emitting diodes (LEDs) owing to their precisely tunable bandgaps, high photoluminescence (PL) efficiency, and excellent color purities. However, the performance of pure red (630-640 nm) all-inorganic perovskite LEDs is still limited by the halide segregation-induced instability of the electroluminescence (EL) of mixed halide CsPbI3-xBrx NCs. Herein, we report an effective approach to improving the EL stability of pure red all-inorganic CsPbI3-xBrx NC-based LEDs via the passivation of potassium bromide on NCs. By adding potassium oleate to the reaction system, we obtained potassium bromide surface-passivated (KBr-passivated) CsPbI3-xBrx NCs with pure red PL emission and a photoluminescence quantum yield (PLQY) exceeding 90%. We determine that most potassium ions present on the surface of NCs bind with bromide ions and thus demonstrate that potassium bromide surface passivation of NCs can both improve the PL stability and inhibit the halide segregation of NCs. Using KBr-passivated CsPbI3-xBrx NCs as an emitting layer, we fabricated stable and pure red perovskite LEDs with emission at 637 nm, showing a maximum brightness of 2671 cd m-2, maximum external quantum efficiency of 3.55%, and good EL stability. The proposed KBr-passivated NC strategy will open a new avenue for fabricating efficient, stable, and tunable pure color perovskite NC LEDs.All-inorganic lead halide perovskite nanocrystals (NCs) are potential candidates for fabricating high-performance light-emitting diodes (LEDs) owing to their precisely tunable bandgaps, high photoluminescence (PL) efficiency, and excellent color purities. However, the performance of pure red (630-640 nm) all-inorganic perovskite LEDs is still limited by the halide segregation-induced instability of the electroluminescence (EL) of mixed halide CsPbI3-xBrx NCs. Herein, we report an effective approach to improving the EL stability of pure red all-inorganic CsPbI3-xBrx NC-based LEDs via the passivation of potassium bromide on NCs. By adding potassium oleate to the reaction system, we obtained potassium bromide surface-passivated (KBr-passivated) CsPbI3-xBrx NCs with pure red PL emission and a photoluminescence quantum yield (PLQY) exceeding 90%. We determine that most potassium ions present on the surface of NCs bind with bromide ions and thus demonstrate that potassium bromide surface passivation of NCs can both improve the PL stability and inhibit the halide segregation of NCs. Using KBr-passivated CsPbI3-xBrx NCs as an emitting layer, we fabricated stable and pure red perovskite LEDs with emission at 637 nm, showing a maximum brightness of 2671 cd m-2, maximum external quantum efficiency of 3.55%, and good EL stability. The proposed KBr-passivated NC strategy will open a new avenue for fabricating efficient, stable, and tunable pure color perovskite NC LEDs.